Service Quality Failure and Recovery Imperatives: Implications for Airlines Owned by South Africa - Mantey, Nicholas O.; Naidoo, Vannie (Journal of Economics and Behavioral Studies, 2016)
This article reports on a study that examined service quality and recovery among South African airlines. Service quality is pivotal in the airline industry as service failures could negatively affect operations. The authors created the acronym â€œAOSAâ€ which stands for â€œairlines owned by South Africaâ€ for the purposes of anonymity and confidentiality in order to protect the airlinesâ€™ identity. A quantitative research approach was used with a cross-sectional analysis (sample survey) conducted with passengers of South African-owned airlines. The questionnaire was designed using a Likert scale tool, adapted to the SERVQUAL model. A non-probability convenient sampling method was used to collect primary data from 684 passengers at O.R.Tambo International Airport in Johannesburg and King Shaka International Airport in Durban. The key findings were that: (1) significant statistical gaps exist between passengersâ€™ expectations and perceptions of AOSAâ€™s service quality and that unsatisfactory service quality is antecedent to service failure. (2) Unsatisfactory service quality is tantamount to service failure in the provision of services by AOSA. (3) A significant positive correlation exists between service quality and the dimensional variables of tangibility, reliability, responsiveness, assurance, and empathy of AOSA. In conclusion, AOSA service quality is unsatisfactory, and management should take steps to empower and train staff in service recovery techniques in other to avoid service failures.